2021
DOI: 10.1002/vetr.771
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of veterinarians at different career stages: The role of self‐efficacy, coping strategies and personal resources for resilience in veterinary practice

Abstract: Background:The aim of this study was to determine the effect of demographic and psychological factors on resilience in new graduate-, mid-and late-career veterinarians working in Australia. Method: An online cross-sectional survey of 800 veterinarians collected demographic and descriptive data in two stages from late 2015 to 2017, such as gender, average hours worked per week, type and region of practice and intention to leave veterinary medicine. Psychological factors were measured utilising the Brief Resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…In light of the current workforce shortage of veterinarians, it is concerning that almost two thirds of respondents had considered leaving their principal area of practice within the past year, with a third wishing to leave the veterinary profession altogether. This finding was in line with a previous 2017 study that showed 27% of sampled experienced veterinarians were at risk of leaving the industry in the next 3 years ( 87 ) A study performed by Montoya et al ( 20 ) interviewed 26 former veterinarians on their reasons for leaving clinical practice. This qualitative study showed that there were a variety of interplaying personal reasons (negative personal thoughts, physical and mental health) and work-related factors (employment conditions including relationship with colleagues, remuneration, working hours and negative clinical outcomes) ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…In light of the current workforce shortage of veterinarians, it is concerning that almost two thirds of respondents had considered leaving their principal area of practice within the past year, with a third wishing to leave the veterinary profession altogether. This finding was in line with a previous 2017 study that showed 27% of sampled experienced veterinarians were at risk of leaving the industry in the next 3 years ( 87 ) A study performed by Montoya et al ( 20 ) interviewed 26 former veterinarians on their reasons for leaving clinical practice. This qualitative study showed that there were a variety of interplaying personal reasons (negative personal thoughts, physical and mental health) and work-related factors (employment conditions including relationship with colleagues, remuneration, working hours and negative clinical outcomes) ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies of general and veterinary populations have shown higher resilience (or reduced perceived stress) in males. 6,9,46,50 Age 6,9,46,50 and veterinary career stage 17 have also been found to have positive associations with resilience. Veterinarians who are younger and early to midcareer might benefit from additional support to help them develop skills to improve their capacity to recover from stressful situations.…”
Section: Discussionmentioning
confidence: 94%
“…12,16 Levels of resilience can vary for an individual over time and by circumstances. 12,16,17 Those who experience repeated environmental and psychological stressors without adequate recovery time can experience reduced resilience and broad physiologic changes associated with chronic stress; the cumulative burden of these stressors is referred to as allostatic load. 16,18,19 To develop a resilient veterinary workforce, it is important to understand effective coping strategies as well as factors that contribute to greater resilience and attend to issues of allostatic load.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Researchers advocated allowing students to develop important resources, e.g., reflective skills, a pro-active attitude, and self-efficacy [28]. Another study investigating veterinary students also found that self-efficacy and coping strategies influence the resilience of graduated veterinarians [90], reducing veterinary-specific occupational stressors. Documented by the time-dose effect and possibly associated with the LOC item "Horse kick", participants became less confident about regaining their health after an animal-related injury (seen in a decreasing agreement to the item "In the profession of veterinary medicine, it is possible to be injured by animals while working (human-animal interaction): Given that, I am still confident of getting well again during my career as a veterinarian").…”
Section: Self-efficacymentioning
confidence: 99%